LAUT YANG MENYATUKAN: MENGUNGKAP RUANG-JEJARING LAUT NUSANTARA - Alex John Ulaen (Fakultas Ilmu Budaya universitas Hasanuddin, 2017)
Maritime transportation has a role in unifying one coastal area with another and allowing population mobility. The arrivals of various communities, both Indonesians and from overseas in the coastal cities of Sulawesi and Maluku have taken place since five centuries ago. One thing can be noted is that the maritime networks did not only facilitate population mobility but also allowing them to be closer to their new host communities. The concept of merantau (migrating) that is still strong is one reason for national integration. In principle, migrants would not forget their origins even though they adiminstratively registered as citizens of their migration destination areas. The returning-home traditon in every religious holidays would activate shipping and would benefit shipping enterprises which connect one island (port) with another.